2022
DOI: 10.1007/s11845-022-03202-8
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of adverse events on urology trainees

Abstract: Introduction Adverse events (AE) are an inevitable reality in healthcare, with an incidence of 7.5-14.1% worldwide. AEs are recognised to cause psychological and emotional distress in healthcare workers, with surgeons being particularly susceptible. We report the first data on the emotional impact in relation to adverse events in surgeons in the Republic of Ireland (ROI). Methods We distributed a web-based survey to all urology trainees in the ROI. The questionnaire focused on trainees' personal account of AEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
(60 reference statements)
3
9
0
Order By: Relevance
“…These adverse events had a significant emotional and psychological toll on the affected surgeon, with some effects even lasting more than two years. Negative effects on subsequent clinical practice such as defensive practice, decreased job satisfaction was also reported by previous studies in this area [ 15 , 16 , 22 , 25 27 ]. Commonly reported emotions in this study, including sadness, guilt, anxiety and embarrassment, was echoed by previous studies as well [ 10 12 , 14 , 16 , 22 , 25 , 28 ].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…These adverse events had a significant emotional and psychological toll on the affected surgeon, with some effects even lasting more than two years. Negative effects on subsequent clinical practice such as defensive practice, decreased job satisfaction was also reported by previous studies in this area [ 15 , 16 , 22 , 25 27 ]. Commonly reported emotions in this study, including sadness, guilt, anxiety and embarrassment, was echoed by previous studies as well [ 10 12 , 14 , 16 , 22 , 25 , 28 ].…”
Section: Discussionsupporting
confidence: 68%
“…Negative effects on subsequent clinical practice such as defensive practice, decreased job satisfaction was also reported by previous studies in this area [ 15 , 16 , 22 , 25 27 ]. Commonly reported emotions in this study, including sadness, guilt, anxiety and embarrassment, was echoed by previous studies as well [ 10 12 , 14 , 16 , 22 , 25 , 28 ]. Although not explored in this study, several factors may affect the extent of emotional sequelae.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This finding is consistent with 2 prior survey studies, which found that trainees felt unprepared to cope with the personal impact of complications and would welcome formal instruction. 48 , 49 There are several potential ways in which surgical training programs could incorporate this component of professional development. For instance, setting expectations about the inevitability of adverse events early in training would likely promote destigmatization.…”
Section: Discussionmentioning
confidence: 99%